KONSTRIBUSI KESEIMBANGAN DAN KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN SERVIS BAWAH PADA PERMAINAN BOLA VOLI SISWA SMP NEGERI 8 MIMIKA - Yolanda Silitubun (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
Service is the most important thing in volleyball. Servicing in volleyball requires certain conditions as capital in serving, including having adequate physical conditions in the form of balance and arm muscle strength. The purpose of this study was to determine how much balance and arm muscle strength contribute to the lower serve ability in volleyball games for students of SMP Negeri 8 Mimika. The type of research used is descriptive correlation and inferential research with balance and arm muscle strength as independent variables, while lower serve ability is the dependent variable. The results showed that: 1) there was a significant contribution between balance on the ability to serve down in volleyball for class VIII students of SMP Negeri 8 Mimika by 13.7%, with a value of rxy (count) = 0.370 > r table (0.05) (30) = 0.361; 2) there is a significant contribution between arm muscle strength and lower serve ability in volleyball games for class VIII SMP Negeri 8 Mimika students of 11.9%, with rxy (count) = 0.385 > r table (0.05) (30) = 0.361. Based on these results, it can be concluded that there is a significant positive contribution between balance and arm muscle strength on the lower serve ability in volleyball games for class VIII SMP Negeri 8 Mimika students.